2022
DOI: 10.1097/md.0000000000028863
|View full text |Cite
|
Sign up to set email alerts
|

Weekly nanoparticle albumin-bound paclitaxel and paclitaxel for relapsed small cell lung cancer

Abstract: In addition to advanced non-small cell lung cancer, nanoparticle albumin-bound paclitaxel (nab-PTX) may also harbor potential benefit for patients with relapsed small cell lung cancer (SCLC), since weekly paclitaxel (PTX) shows modest activity for relapsed SCLC. We evaluated the efficacy and safety of both weekly nab-PTX and PTX for relapsed SCLC.We retrospectively reviewed 52 consecutive relapsed SCLC patients who were treated with weekly nab-PTX or PTX at our hospital.The response rate, median progression-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, a phase II NABSTER prospective trial of nab‐PTX did not meet its primary endpoint, with an ORR of 11.8% and DCR of 30.9% in patients who progressed to first‐line chemotherapy 24 . The results for nab‐PTX alone for relapsed ES‐SCLC from retrospective studies remained variable, with ORR of 5.6–29.4%, DCR of 44.4–81.1%, median PFS of 1.6–5.0 months, and median OS of 4.0–9.0 months, but lacking large sample data and drug comparisons 25–28 . It is therefore inconclusive whether or not nab‐PTX alone can be used in second‐line or subsequent‐lines treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a phase II NABSTER prospective trial of nab‐PTX did not meet its primary endpoint, with an ORR of 11.8% and DCR of 30.9% in patients who progressed to first‐line chemotherapy 24 . The results for nab‐PTX alone for relapsed ES‐SCLC from retrospective studies remained variable, with ORR of 5.6–29.4%, DCR of 44.4–81.1%, median PFS of 1.6–5.0 months, and median OS of 4.0–9.0 months, but lacking large sample data and drug comparisons 25–28 . It is therefore inconclusive whether or not nab‐PTX alone can be used in second‐line or subsequent‐lines treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 24 The results for nab‐PTX alone for relapsed ES‐SCLC from retrospective studies remained variable, with ORR of 5.6–29.4%, DCR of 44.4–81.1%, median PFS of 1.6–5.0 months, and median OS of 4.0–9.0 months, but lacking large sample data and drug comparisons. 25 , 26 , 27 , 28 It is therefore inconclusive whether or not nab‐PTX alone can be used in second‐line or subsequent‐lines treatment. Similar to the clinical trial of pembrolizumab plus paclitaxel by Kim et al, 19 our data for ICIs plus paclitaxel (mainly nab‐PTX) also showed a favorable antitumor effect for ES‐SCLC in second‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PTX is one of the most frequently prescribed medications in Japanese clinical practice to treat recurrent SCLC and the efficacy of nanoparticle albumin-bound (nab)-PTX monotherapy might be moderate for heavily treated, relapsed SCLC patients (19). Several studies reported the use of PTX combined with carboplatin, gemcitabine or albumin-bound PTX nanoparticles for the treatment of metastatic or recurrent SCLC, indicating that PTX as second-line chemotherapy is a good choice for the treatment of patients with SCLC (48)(49)(50). After nano-microsized modification, PTX is an ideal drug for the treatment of SCLC due to its improved therapeutic efficiency and diminished side effects.…”
Section: Iron Oxide Nanoparticles Induce Ferroptosis Via the Autophag...mentioning
confidence: 99%
“…Paclitaxel was initially approved by the U.S. Food and Drug Administration (FDA) in 1992 for the treatment of ovarian cancer and in 1994 for the treatment of metastatic breast cancer [6]. In subsequent years, it has also been approved to treat non-small cell lung carcinoma, AIDS-related Kaposi's sarcoma and cancers of the lung, bladder, esophagus, prostate and pancreas, either alone or in combination with other anticancer drugs [7,8]. It has been clinically proven that paclitaxel has good anti-tumor effects, especially for ovarian cancer, uterine cancer and breast cancer, which have a high incidence of occurrence [9].…”
Section: Introductionmentioning
confidence: 99%